PO074 The devastating thalamic stroke tremor: does dbs help?. (1st December 2017) - Alusi, Sundus; Bonello, Michael; Tambirajoo, Kantharuby; Hammersley, Beth; Lowry, Lindsey; Das, Kumar; Eldridge, Paul; Farah, Jibril
Abstract : Latero-posterior thalamic strokes are reported to result in delayed onset action tremor, dystonia, pseudoathetosis, chorea and myoclonus. This complex disorder is usually associated with proprioceptive sensory loss and limb ataxia. The tremor has a large amplitude postural component whichworsens on targeted movements; this with the associated sensory loss renders it incapacitating. Thalamic VIM ablation has been reported to improve this tremor. However, deep brain stimulation (DBS) has not. We report 3 cases with post-thalamic stroke tremor, 2 of which have been successfully treated with thalamic DBS; the third is being considered. The first was a 41 year old female who presented with a left sided tremor resulting from a right thalamic stroke after a vertebral artery dissection. The second was a 69 year old male with a right sided tremor resulting from an ischaemic stroke of the left thalamus and the third had bilateral arm tremor resulting from bilateral latero posterior thalamic strokes following a syringomyelia decompression surgery. The tremor in all was of the cerebellar type with joint position sense loss up to the wrist; pseudoathetosis and dystonic posturing. Thalamic DBS ameliorated the large amplitude component of the tremor improving arm function.